1999
DOI: 10.1090/s0025-5718-99-01129-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of elliptic curves over certain real quadratic number fields

Abstract: Abstract. The main result of this paper is that an elliptic curve having good reduction everywhere over a real quadratic field has a 2-rational point under certain hypotheses (primarily on class numbers of related fields). It extends the earlier case in which no ramification at 2 is allowed. Small fields satisfying the hypotheses are then found, and in four cases the non-existence of such elliptic curves can be shown, while in three others all such curves have been classified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 5 publications
3
10
0
Order By: Relevance
“…This is true only if E has a K-rational point of order 2. Thus we showed that This extends results of Pinch [13] and Kida [7]. An elliptic curve E over K is called admissible if the following conditions are satisified:…”
Section: A List Of Pairs Not Satisfying ( †)supporting
confidence: 84%
“…This is true only if E has a K-rational point of order 2. Thus we showed that This extends results of Pinch [13] and Kida [7]. An elliptic curve E over K is called admissible if the following conditions are satisified:…”
Section: A List Of Pairs Not Satisfying ( †)supporting
confidence: 84%
“…For the values of m above such that the class number of Q m p is prime to 6, that is, for m 2, 3, 5, 6, 7, 13, 14, 17, 21, 41, 47, 73, 94, 97, the same results have already been obtained in [2], [4], [5], [10]. It is worth remarking that we use the class field theory only, whereas the authors of [2], [4] and [5] used Serres results on Galois representation theory ( [11]) or the ramification theory in Kummer extensions in addition.…”
Section: Appendixsupporting
confidence: 68%
“…We also deal with many other fields in Appendix, where we use similar arguments given in section 3.1 in order to simplify the arguments in our previous papers [2], [4], [5], [10].…”
mentioning
confidence: 99%
“…This result is further generalized to certain quadratic fields and some other fields (see [9] and the references there).…”
Section: Introductionmentioning
confidence: 72%